Pembuatan Perangkat Pembelajaran Berbasis Modul pada Mata Pembelajaran Gambar Teknik Manufaktur Kelas XI TPM - Utami, Fathya Suci; Sari, Delima Yanti; Purwantono, Purwantono; Adri, Junil (MASALIQ, 2023)
Learning in several vocational schools uses Autodesk software which has many features and is also widely used in industry. The change in the use of the 2013 curriculum at SMK N 5 Padang will certainly change the learning concept which originally used the 2013 curriculum to become an independent curriculum. Curriculum changes require teachers to prepare new media or teaching materials in accordance with the established curriculum. The aim to be achieved in the research is to develop a PJBL (Project Based Learning) based learning tool for the Manufacturing Engineering Drawing subject with the hope that this module can be used in schools as a learning medium. This research uses the R&D method with the ADDIE development model. Material expert validation was carried out by 3 experts in the field of production materials. The percentage of presentation aspects is 1.0 and the percentage of content aspects is 0.97. The percentage of validation results for all aspects is 0.98 in the very valid category. Validation of media experts and models was carried out by 3 experts in the media field. The percentage of the visual appearance aspect is 0.96, the physical criteria aspect is 0.93 and the convenience aspect is 1.0. The percentage of media expert validation results from all aspects is 0.96, very valid research category. Language expert validation was carried out by 1 expert in the field, consisting of 8 items. The percentage of language expert validation is 0.87 in the very valid category, so this teaching module is said to be very good for use in the learning process by future researchers.